KOMUNITAS DAN INSTITUSI SOSIAL MUSLIM DI INDONESIA (Telaah Historis atas Pembentukan dan Perkembangannya) - Jaelani Jaelani (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2020)
The formation of Muslim social institutions and communities in Indonesia has become a part of the history of Islam in the region. Islam as a doctrine has given color to the formation of a new culture in Indonesian society. In this case, the formation of Muslim social institutions and communities and their development goes through stages similar to the evolutionary process of Islamization. At the stage of the development of Muslim social institutions, for example, this is the actualization of the appreciation and deepening of Islamic teachings on the one hand and interactions with other communities on the other. The dynamics of Muslim social institutions and communities and their development until now is a process that will continue throughout the ages.